MORPHO-PHYSIOLOGICAL DIVERSITY IN ADVANCED LINES OF BREAD WHEAT UNDER DROUGHT CONDITIONS AT POST-ANTHESIS STAGE - M. A. Ali; M. Zulkiffal; J. Anwar; M. Hussain; J. Farooq; S. H. Khan (Journal of Animal and Plant Sciences, 2015)
Fifty two advanced lines of bread wheat including 6 approved varieties were used to study morpho-physiological diversity under drought conditions at post-anthesis stage based on 18 plant characters. A multivariate approach including correlation, principal component and cluster analysis was used to quantify the variability among the wheat lines. Correlation analysis showed that grain yield was positively correlated with yield attribute like head weight, spike length, spikelets per spike, grains per spike, days to heading and days to maturity. Grain yield, on the other hand, did not show any positive association with physiological traits. Relative water content was positively correlated with head weight and negatively associated with excised leaf weight loss. Head weight was negatively correlated with residual transpiration. Principal component (PC) analysis resulted in six principal components (PCs) having Eigen value >1 which contributed 70.908% of the total variability amongst the wheat genotypes assessed for various morph-physiological traits. The PC I contributed maximum towards the variability (24.108%) and this variability was mainly conditioned by yield attributes like spikelets per spike, grains per spike, days to heading, head weight, flag leaf area, spike length and grain yield. PC analysis also supported the results of correlation analysis that yield components were not correlated with the physiological characters. Cluster analysis grouped 52 genotypes into 4 clusters. Cluster 1 comprised of 17 genotypes, cluster 2 of 16 while cluster 3 had 6 and cluster 4 contained 13 genotypes. Cluster 1 comprised of lines having high values for grain yield attribute, while cluster 2 lines showed drought tolerance characters like high relative water content and less residual transpiration. Altogether, this research showed that enormous amount of morpo-physiological variation was present in this group of genotypes which could be helpful for selection of favourable cultivars for drought tolerance in bread wheat.
Keywords: Bread wheat; drought tolerance; morpho-physiological traits; multivariate analysis